Notch3 Targeting: A Novel Weapon against Ovarian Cancer Stem Cells. (6th January 2019) - Ceccarelli, Simona; Megiorni, Francesca; Bellavia, Diana; Marchese, Cinzia; Screpanti, Isabella; Checquolo, Saula
Abstract : Notch signaling is frequently activated in ovarian cancer (OC) and contributes to the proliferation and survival of cultured OC cells as well as to tumor formation and angiogenesis in xenograft models. Several studies demonstrate that Notch3 expression renders cancer cells more resistant to carboplatin, contributing to chemoresistance and poor survival of OC-bearing patients. This suggests that Notch3 can represent both a biomarker and a target for therapeutic interventions in OC patients. Although it is still unclear how chemoresistance arises, different lines of evidence support a critical role of cancer stem cells (CSCs), suggesting that CSC targeting by innovative therapeutic approaches might represent a promising tool to efficiently reduce OC recurrence. To date, CSC-directed therapies in OC tumors are mainly targeted to the inhibition of CSC-related signaling pathways, including Notch. As it is increasingly evident the involvement of Notch signaling, and in particular of Notch3, in regulating stem-like cell maintenance and expansion in several tumors, here we provide an overview of the current knowledge of Notch3 role in CSC-mediated OC chemoresistance, finally exploring the potential design of innovative Notch3 inhibition-based therapies for OC treatment, aimed at eradicating tumor through the suppression of CSCs.